Biogenic Synthesis and Spatial Distribution of Endogenous Phytohormones and Ginsenosides Provide Insights on Their Intrinsic Relevance in Panax ginseng - Chen, Kang; Liu, Juan; Ji, Ruifeng; Chen, Tong; Zhou, Xiuteng; Yang, Jian; Tong, Yuru; Jiang, Chao; Zhou, Junhui; Zhao, Yuyang; Jin, Yan; Yuan, Yuan; et al. (Frontiers in Plant Science, 2019)
Ginseng, the root and rhizome of Panax ginseng C. A. Mey., is a well-known and valuable traditional Chinese medicine. The pharmacological activities of ginseng are mainly attributed to the presence of ginsenosides, which are considered to be critical biomarkers for evaluating ginseng quality. The biosynthesis of triterpenes, which serve defensive functions in plants, is regulated by endogenous phytohormones that play key roles in growth and defense of plant populations. However, the role of major hormones that are closely related to secondary metabolism pathways in P. ginseng is poorly understood. To gain insight into their potential correlation, we performed a spatial synthesis analysis and studied the distribution of endogenous phytohormones and ginsenosides in different tissue regions of the entire P. ginseng plant. Gibberellins are growth hormones that accumulate in the fiber root. In contrast, abscisic acid, salicylic acid, and jasmonic acid, which are considered stress hormones, were predominantly found in the leaf and leaf peduncle. We observed a tissue-specific distribution of phytohormones consistent with the expression of genes involved in hormone biosynthesis that influenced ginsenoside synthesis and distribution. The aim of this study was to investigate the role of different endogenous phytohormones on triterpene metabolites in ginseng innate immunity.